Genome wide significant linkage in schizophrenia conditioning on occurrence of depressive episodes. Issue 7 (14th October 2005) - Hamshere, M L; Williams, N M; Norton, N; Williams, H; Cardno, A G; Zammit, S; Jones, L A; Murphy, K C; Sanders, R D; McCarthy, G; Gray, M Y; Jones, G; et al.
Abstract : Background: Schizophrenia shows substantial clinical heterogeneity. One common important clinical variable in presentation is the occurrence of episodes of major depression. Methods: We undertook analyses in an attempt to detect loci that influence susceptibility to, or modify the clinical expression of, schizophrenia according to the occurrence of episodes of major depression. We used a logistic regression framework in which lifetime presence/absence of major depression was entered as a covariate in the linkage analysis of our UK schizophrenia affected sibling pair series (168 affected sibling pairs typed for a 10 cM map of microsatellite markers). Results: Inclusion of presence/absence of depression as a covariate detected a genome wide significant linkage signal on chromosome 4q28.3 at 130.7 cM (LOD = 4.59; p = 0.038; increase in maximum LOD over univariate analysis (ILOD) = 3.62). Inclusion of the depression covariate also showed suggestive evidence of linkage on 20q11.21 (LOD = 4.10; expected to occur by chance 0.093 times per genome scan, ILOD = 2.83). Conclusions: Our findings identify loci that may harbour genes that play a role in susceptibility to, or modify the risk of, episodes of major depression in people with schizophrenia.